The chieftains in the last phase of the Kandyan Kingdom (Sinhalé) - Pilimatalavuva, Ananda (Pannipitiya : Stamford Lake Publication, 2008)
Collective biographies of chieftains of Sri Lanka in late 18th century and the political conditions of their times.
Keywords: Nobility